ANALISIS PEMASARAN JAMUR TIRAM PUTIH (PLEUROTUS OSTREATUS) PADA UMKM ELOK MEKARSARI DI SEMOLOWARU, KECAMATAN SUKOLILO SURABAYA - Junior, Gordianus Jimi; Krisna Dianto, Andri (Jurnal Agribisnis Wijaya Putra Surabaya, 2024)
ABSTRACT This study aims to analyze the marketing strategy implemented by Mekarsari Micro, Small and Medium Enterprises (MSMEs) engaged in the production and sale of white oyster mushrooms in the Semolowaru area, Sukolilo District, Surabaya. White oyster mushroom is a product that is increasingly in demand in local and regional markets because of its health benefits and distinctive taste. This study was conducted using a qualitative descriptive research method. Qualitative data were obtained through in-depth interviews with MSME owner Elok Mekarsari and a number of 3 workers. Meanwhile, data was collected through a survey using a questionnaire distributed to Elok Mekarsati UMKM workers or members. The results showed that the Mekarsari UMKM marketing system used 2 marketing channels, namely channel 1 consisting of white oyster mushroom producers, final consumers while channel 2 marketing channels consisted of white oyster mushroom producers, wholesalers, final consumers. the marketing system that has been implemented 5P (Marketing Mix) product, price, place, promotion, people includes promotions through social media, trade shows, and cooperation with restaurants and supermarkets local. Apart from that, they also provide special offers for loyal customers to increase customer retention. However, even though there have been marketing efforts made, there are still several obstacles faced by Elok Mekarsari's MSMEs. Some of these obstacles include intense competition with other white oyster mushroom producers, difficulties in accessing export markets, and limited capital for wider promotion.